2014
DOI: 10.1177/1087054714527792
|View full text |Cite
|
Sign up to set email alerts
|

ADHD Symptomatology and Risky Health, Driving, and Financial Behaviors in College

Abstract: The current study provides initial data showing potentially different mechanisms that explain the link between college students' severity of ADHD symptoms and risky behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 81 publications
0
43
0
1
Order By: Relevance
“…Dopamine activity in the reward processing network has also been shown to underlie sensation seeking . Along with greater disinhibition and delay discounting, high sensation seeking has also been found to characterize individuals with SUD as well as young adults with ADHD . Together, these overlapping findings demonstrate that high impulsivity is a predominant shared trait in ADHD and SUD and have steered most of the emerging neuroimaging research on high‐risk ADHD to focus on the underlying inhibitory control and motivation‐reward processing brain networks …”
Section: Impulsivity As a Linking Mechanismmentioning
confidence: 95%
“…Dopamine activity in the reward processing network has also been shown to underlie sensation seeking . Along with greater disinhibition and delay discounting, high sensation seeking has also been found to characterize individuals with SUD as well as young adults with ADHD . Together, these overlapping findings demonstrate that high impulsivity is a predominant shared trait in ADHD and SUD and have steered most of the emerging neuroimaging research on high‐risk ADHD to focus on the underlying inhibitory control and motivation‐reward processing brain networks …”
Section: Impulsivity As a Linking Mechanismmentioning
confidence: 95%
“…Within a large student sample, Graziano et al [82] showed an association between the severity of ADHD symptoms and risky behavior but only when EC was low. However, it needs to be noted that this study relates to ADHD symptoms (as assessed with a screening instrument) and not to individuals with a formal ADHD diagnosis.…”
Section: Ec and Adhdmentioning
confidence: 99%
“…[9] Even more troubling, such individuals are prone to impulsive and risky behaviors including substance abuse, self-inflicted injury, and suicide attempts. [10,11] These sequelae are observed even among those who received effective treatment in childhood. [12].…”
Section: Introductionmentioning
confidence: 99%
“…[9] In addition, symptoms of ADHD among college students are associated with compulsive credit card use. [10]. Such outcomes, combined with spotty employment histories, likely contribute to high rates of financial distress reported by adults with ADHD.…”
Section: Introductionmentioning
confidence: 99%